NMR analysis of budding yeast metabolomics: a rapid method for sample preparation. Issue 2 (21st October 2014) - Airoldi, C.; Tripodi, F.; Guzzi, C.; Nicastro, R.; Coccetti, P.
Abstract : We present a rapid and reproducible protocol for intracellular metabolite extraction from yeast cells analyzed by 1 H-NMR spectroscopy. Abstract : Here we propose the optimization of a rapid and reproducible protocol for intracellular metabolite extraction from yeast cells and their metabolic profiling by 1 H-NMR spectroscopy. The protocol reliability has been validated through comparison between the metabolome of cells in different phases of growth or with different genetic backgrounds.